CSI Effect of Crime Clarification - Yakupoğlu, Aylin; Çalıcı, Can; Ziyalar, Neylan (The Bulletin of Legal Medicine, 2016)
Objective: This research is aimed to evaluate the impact of CSI series on Criminal Justice Professional’s attitudes and behaviour and how these programs effecting public. From this point of view criminal justice professionals are expected to respond questions about, how this kind of dramas and programs guided potential criminals, reflected the practice of forensic science and directed the public expectation regarding performing their professions. Material and Methods: A survey has been conducted to 266 participants, who are working as crime scene investigation specialists, criminal courts judges, public prosecutors, lawyers, law enforcement personnel and forensic specialists, to reveal their perceptions. Gained data has been analyzed statistically by using SPSS (Version 20.0). Findings: According to some results of the research; 1 out of every 2 participants are following CSI series. only 3 out of every 10 participants expressed that these kind of series have positive effects on their professional practices, more than half of the participants agreed that crime dramas are effecting criminal behaviour and creating trained perpetrators. Also 1 out of every 2 participants believe that the perpetrators are attentive to leave fewer evidence because of these programs. Results: CSI series are not reflecting forensic techniques and methods as what it’s supposed to be in real life. Due to the raise of public interest in forensic sciences because of these dramas people changed their expectation about criminal justice mechanism which can be cause misperceptions on citizens who face with investigation and prosecution processes for the first time Keywords: CSI Effect; Crime Scene Investigation; Forensic Techniques and Methods